Waqf and Bayt Al-Hikmah: A Review - Puspita, Amelia Tri (SMART Insight, 2023)
Caliph Al-Ma'mun was the first individual to come up with the idea of establishing a waqf body to finance education and built the world's first waqf-funded institution called Bayt al-Hikmah. The early establishment of Bayt al-Hikma as a concept or indeed as a forum for debate can be attributed to Harun ar-Rashid (763-809 CE) who regularly held intellectual debates with scholars and scientists. This study aims to determine the development of waqf and Bayt al-Hikmah research trends published by leading journals on Islamic economics. The data analyzed consisted of 117 indexed research publications. The data is then processed and analyzed using the VoS viewer application to determine the bibliometric map of waqf and Bayt al-Hikmah research development.